NEW ONSET DIABETES BEFORE AND DURING THE COVID-19 PANDEMIC AND FACTORS ASSOCIATED WITH DIABETIC KETOACIDOSIS IN SELECTED TERTIARY HOSPITALS - Nasir, Fatin Farihah Wan Ahmad; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar; Selveindra, Nalini; Lim, Poi Giok; Lee, Yee Lin (Journal of the ASEAN Federation of Endocrine Societies, 2023)
NTRODUCTIONIntroduction New onset diabetes mellitus (DM) and diabetic ketoacidosis (DKA) among children have increased worldwide following the COVID-19 pandemic. This study aimed to determine the frequency of new-onset DM and DKA during the COVID-19 pandemic as compared to the pre-pandemic period and to determine the factors associated with DKA among children with new onset DM. METHODOLOGY A cross-sectional retrospective study was conducted at four paediatric endocrine tertiary hospitals in Klang Valley, Selangor among all patients with new-onset diabetes during two-time intervals, 2015 to 2019 (before the pandemic) and 2020 to 2022 (during the pandemic). Data on patients’ demographics and clinical characteristics were collected. RESULT Three hundred eighty-eight patients with new onset DM were included. Both new-onset DM and DKA showed increased relative frequencies after the onset of the pandemic (17.2% in 2021, 14.1% in 2020, 11.2% in 2019, 12.8% in 2018) and (18.5% in 2021, 16.2% in 2020, 9.3% in 2019, 10.3% in 2018) respectively. The relative frequencies of patients with newonset type 1 diabetes mellitus (TIDM) increased during the pandemic, but type 2 diabetes mellitus (T2DM) cases declined. Median BMI was found to be higher among patients with new-onset T2DM during the pandemic compared to those who developed T2DM pre-pandemic (p=0.04). Patients with T2DM also had sa horter duration of symptoms (p=0.019) and lower HbA1c (p=0.008) during the pandemic. On multiple logistic regression, a younger age, lower BMI, T1DM, higher blood glucose and higher HbA1c were factors significantly associated withnew-onsett DKA. CONCLUSION There was an increase in Type 1 DM and DKA following the pandemic. Awareness of at-risk groups and associated clinical characteristics enables early detection of new-onset DKA and DM. Early surveillance of T2DM among persons with higher BMI should be emphasised. Public health education and campaigns for lifestyle modification, infection control precautions and COVID-19 vaccination should be actively implemented.